Analisis Investigasi Faktor-faktor yang Mempengaruhi Kemampuan Perusahaan dalam Pembayaran Dividen - Dyah Rosna Yustanti Toin; Sutrisno Sutrisno (Jurnal Aplikasi Bisnis, 2017)
There are two conflicting interests in the use of corporate profits, the first for the payment of dividends to shareholders, second for the benefit of corporate development. For that reason managements should take the form of dividend policy how much dividend to be distributed and how much profit will he used for the development of the company (retained earnings).This study aims to examine the factors that affect the ability of companies in the payment of dividends. Proxy for ability to pay dividends is measured with Dividend Payout Ratio (DPR) as dependent variable, while the independent variables are profitability (XI), liquidity (X2), Leverage (X3), and the Firm's growth (X4).The results showed that the profitability variable has a statistically I significant and positive correlation with the ability to pay dividends. Likewise, the variable of firm's growth is statistically also has negative and significant correlation with the dividend payout ratio. While the variables liquidity and leverage have statistically not significant correlation with the dividend payment.It can he concluded that in this study there are two variables that support the hypothesis that profitability and firm's growth, while two other variables do not support the hypothesis that liquidity and leverage.